Synthesis of Site-Specific Antibody-[60]Fullerene-Oligonucleotide Conjugates for Cellular Targeting - Äärelä Antti; Räsänen Kati; Holm Patrik; Salo Harri; Virta Pasi (AMER CHEMICAL SOC, 2025)
An ideal therapeutic antibody-oligonucleotideconjugate(AOC) would be a uniform construct, contain a maximal oligonucleotide(ON) payload, and retain the antibody (Ab)-mediated binding properties,which leads to an efficient delivery of the ON cargo to the site oftherapeutic action. Herein, [60]fullerene-based molecular sphericalnucleic acids (MSNAs) have been site-specifically conjugated to antibodies(Abs), and the Ab-mediated cellular targeting of the MSNA-Abconjugates has been studied. A well-established glycan engineeringtechnology and robust orthogonal click chemistries yielded the desireduniform MSNA-Ab conjugates (MW & SIM; 270 kDa), with an oligonucleotide(ON):Ab ratio of 24:1, in 20-26% isolated yields. These AOCsretained the antigen binding properties (Trastuzumab's bindingto human epidermal growth factor receptor 2, HER2), studied by biolayerinterferometry. In addition, Ab-mediated endocytosis was demonstratedwith live-cell fluorescence and phase-contrast microscopy on BT-474breast carcinoma cells, overexpressing HER2. The effect on cell proliferationwas analyzed by label-free live-cell time-lapse imaging.